Prognostic Significance of the Stage at Which an MRD-Negative Status Is Achieved for Patients With Multiple Myeloma Who Received ASCT - Sun, Qian; Li, Xiaozhe; Gu, Jingli; Huang, Beihui; Liu, Junru; Chen, Meilan; Li, Juan (Frontiers in Oncology, 2022)
Objective To explore the prognostic significance of the stage at which a minimal residual disease (MRD)-negative status is achieved for patients with newly diagnosed multiple myeloma (NDMM) who received autologous hematopoietic stem cell transplantation (ASCT). Cases and Methods A retrospective analysis of 186 NDMM patients who received “induction therapy-ASCT-maintenance therapy” in our center and achieved an MRD-negative status was performed. Patients were divided into three groups, A (induction therapy), B (3 months after ASCT), and C (maintenance therapy), according to the stage at which an MRD-negative status was achieved. Results The median time to progression (TTP) of 186 patients was not reached; the median overall survival (OS) was 113.8 months. The median TTP of the patients in three groups was not reached (P=0.013), and the median OS of the patients in three groups was not reached, not reached, and 71.2 months, respectively (P=0.026). Among patients with standard-risk cytogenetics, the median TTP of those in all three groups was not reached (P=0.121), and the median OS of the patients in three groups was not reached, not reached, and 99.6 months, respectively (P=0.091). Among patients with high-risk cytogenetics, the median TTP of those in three groups was not reached, 53.9 months, and 35.8 months (P=0.060), and the median OS was not reached, 71.2 months, and 60.2 months, respectively (P=0.625). Among patients with R-ISS stage I-II, the median TTP of those in three groups was not reached (P=0.174), and the median OS of the patients in three groups was not reached, not reached, and 99.6 months, respectively (P=0.186). Among the 29 patients with R-ISS stage III, the median TTP of those in the 3 groups were unreached, unreached, and 35.1 months (P<0.001), and the median OS was unreached, unreached, and 48.5 months, respectively (P=0.020). In all enrolled patients, the stage of reaching MRD-negative was an independent prognostic factor for TTP, rather than a prognostic factor for OS. The stage of reaching MRD-negative in patients with R-ISS III was an independent prognostic factor for OS. Conclusion For the same patients who are MRD-negative, the prognoses of those who achieve an MRD-negative status at different groups are different. The stage at which an MRD-negative status is achieved can predict the prognosis of patients with R-ISS stage III.